Pengaruh Gaya Kepemimpinan, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Guru di UPTD SDN 15 Pinang Damai - Fadilla Lesmana; Novrihan Leily Nasution; Aulia Indra (Journal on Education, 2023)
This study aims to analyze the effect of leadership, work environment, and work discipline on teacher performance, partially and simultaneously. Teacher performance plays an important role for the advancement of education in Indonesia, especially in UPTD SDN 15 Pinang Damai, less than optimal teacher performance which results in program targets not being optimal. Given the importance of teacher performance in order to achieve educational goals optimally, encouraging researchers to conduct research with the title "The Effect of Principal Leadership Style, Work Environment and Compensation on Teacher Performance at UPTD SDN 15 Pinang Damai". The type of research used in this research is quantitative research. The results showed that the X1 variable was 0.001, then the X2 variable sig. 0.007, then the X3 variable sig. 0.000. All of these significant values ​​are less than 0.05 which means that the X1 variable, X2 variable, X3 variable partially affects the Y variable. The significance value of F (0.000) < error rate (α = 0.05), then the hypothesis is accepted, so it can be concluded that the three variables together or simultaneously have a significant effect on teacher performance. The R² value of 0.589 or 58.9% indicates that the employee performance variable that can be explained by the three variables is 58.9%, while 41.1% is explained by other factors not included in this study.